Alternative practices of health maintenance in elderly age - Chernyshkova E.V. (Саратовский научно-медицинский журнал, 2011)
The analysis of elderly people attitude to alternative practices of health maintenance in the context of activity prolongation is presented. By the example of conducted sociological research it is demonstrated that besides medication, health resources maintenance includes the following relevant methods: physical exercises and fitness; quit pernicious habits; rational nutrition; sexual activity